2015
DOI: 10.1002/chem.201502208
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene–Phosphinidene Complexes of the Coinage Metals

Abstract: Coinage metal complexes of the N-heterocyclic carbene-phosphinidene adduct IPr⋅PPh (IPr=1,3-bis(2,6-diisopropylphenyl)imidazolin-2-ylidene) were prepared by its reaction with CuCl, AgCl, and [(Me2 S)AuCl], which afforded the monometallic complexes [(IPr⋅PPh)MCl] (M=Cu, Ag, Au). The reaction with two equivalents of the metal halides gave bimetallic [(IPr⋅PPh)(MCl)2 ] (M=Cu, Au); the corresponding disilver complex could not be isolated. [(IPr⋅PPh)(CuOTf)2 ] was prepared by reaction with copper(I) trifluoromethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(104 citation statements)
references
References 140 publications
6
97
1
Order By: Relevance
“…The C carbene –P bond lengths range from 1.805(2) Å (in 4c ) to 1.819(3) Å (in 4b ) and are significantly longer than those in the free ligands [1.7510(16) Å for R = H, 1.7658(10) Å for R = Ph, 1.766(2) Å for R = Mes], in agreement with the expected decrease of the C carbene –P bond order upon metal complexation . The metal–phosphorus bond lengths in the pairs 4a / 4b and 5a / 5b are almost identical, whereas the steric demand of the mesityl substituent in 4c affords a slightly elongated W–P bond (Table ).…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…The C carbene –P bond lengths range from 1.805(2) Å (in 4c ) to 1.819(3) Å (in 4b ) and are significantly longer than those in the free ligands [1.7510(16) Å for R = H, 1.7658(10) Å for R = Ph, 1.766(2) Å for R = Mes], in agreement with the expected decrease of the C carbene –P bond order upon metal complexation . The metal–phosphorus bond lengths in the pairs 4a / 4b and 5a / 5b are almost identical, whereas the steric demand of the mesityl substituent in 4c affords a slightly elongated W–P bond (Table ).…”
Section: Resultssupporting
confidence: 69%
“…In the latter study, it was also shown that cationic digold complexes such as [(IPr · PPh){Au(tht)} 2 ][SbF 6 ] 2 (tht = tetrahydrothiophene) may serve as robust single‐source catalysts in cycloisomerization or carbene‐transfer reactions, and these were the first applications of carbene–phosphinidenes as ancillary ligands in homogeneous catalysis. Moreover, the isolation of the monometallic complexes [(IPr · PPh)MCl] (M = Cu, Ag, Au) indicates that the stepwise complexation of the phosphorus atom in IPr · PPh is possible . This ability was also demonstrated previously by Lavoie, who reported the ruthenium(II) benzylidene complex [{IMes · PPh}RuCl 2 (CHPh)(PPh 3 )] …”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations